1984
DOI: 10.1016/0014-5793(84)81289-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thyroid hormone on the degree of control of oxidative phosphorylation exerted by the adenine nucleotide translocator

Abstract: Impaired phosphorylation efficiency in liver mitochondria from hypothyroid rats is paralleled by a defect in adenine nucleotide transport. Both of these lesions can be corrected within 15 min by a near-physiological dose of triiodo-L-thyronine. Measurement of the control strength of the translocator shows, however, that this step has a smaller share of the control for oxidative phosphorylation after thyroid~tomy and that this is unaltered after 15 min by replacement therapy. Rapid control by triiodothyronine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The effect of T3 on state 4 and state 3 of mitochondrial respiration could be the result of its action on: (a) the concentration of some chain components (Bronk, 1966), (b) substrate dehydrogenase (Lee & Lardy, 1965), (c) adenine nucleotide carrier (Babior et al 1973); Holness et al 1984); even if the action on the latter is noticeable at state 3 respiration (Brand & Murphy, 1987). The current opinion is that the action on the con¬ centration of chain components is of lesser import¬ ance than the activation of substrate dehydrogenase, since hyperthyroidism is associated with increased reduction of the electron transport chain (Brand & Murphy, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of T3 on state 4 and state 3 of mitochondrial respiration could be the result of its action on: (a) the concentration of some chain components (Bronk, 1966), (b) substrate dehydrogenase (Lee & Lardy, 1965), (c) adenine nucleotide carrier (Babior et al 1973); Holness et al 1984); even if the action on the latter is noticeable at state 3 respiration (Brand & Murphy, 1987). The current opinion is that the action on the con¬ centration of chain components is of lesser import¬ ance than the activation of substrate dehydrogenase, since hyperthyroidism is associated with increased reduction of the electron transport chain (Brand & Murphy, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…were reported by . The importance of this to control of electron flux is doubtful, since Holness et al (1984) showed that the flux control coefficient did not drop with short term triiodothyronine treatment, but rose, implying that altered kinetics of the carrier could not be the primary cause of any increase in respiratory rate. These results were similar to those of Verhoeven et al (1985) using 24 h treated rats.…”
Section: ( C ) Short-term Eflectsmentioning
confidence: 99%
“…Mowbray (Palacios-Romero & Mowbray, 1979;Corrigall & Mowbray, 1983 ;Corrigall, Tselentis & Mowbray, 1984;Holness et al, 1984; Mowbray & Crespo-Armas, I 985) has reported that mitochondria from thyroidectomized rats have P/O ratios approximately half that of euthyroid animals, and that treatment with triiodothyronine for 1 5 min reversed this drop. Unfortunately the method of calculation of P/O ratios was that of Chance & Williams (1955), which utilizes extra oxygen consumed in a state 4-3-4 transition, not total oxygen.…”
Section: ( C ) Short-term Eflectsmentioning
confidence: 99%
“…To complement this evidence of a putative receptor, rapid effects of hormone on an energy-driven mitochondrial process such as respiratory control, uncoupler sensitivity [2] and calcium transport [4] have been observed. In our laboratory we have found that liver mitochondria from thyroidectomized rats show a number of altered responses to ADP stimulation that hormone addition at near-physiological concentrations both in vivo and in vitro can restore to normal within 15 min [1, [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%